Evaluation of Potassium Bromate Concentration in different types of Bread collected from several bakeries distributed in Kekla- Libya by Spectral Method - Soad Shibani N. Jaida (African Journal of Advanced Pure and Applied Sciences, 2026)
Arab societies, and particularly Libyan citizens, consume large quantities various types of bread daily. The high level of bread consumption may negatively affect consumers' health due to the presence of several food additives and hazardous chemicals that often exceed the permissible limits in bread products. In this study, nine bread samples including Ciabatta bread, French bread, Barley bread, and Tanour bread were collected from bakeries and markets distributed in the city of Kekla. These samples were analysed to determine the residues of potassium bromate (KBrO3) using a spectrophotometric method depending on the redox reaction between bromate ion in the samples and iodide ion of used reagent solubilized in an acidic medium. The study found that the concentrations of KBrO3 in all studied samples ranged from 10.68 to 35.77 μg/g. This indicated that the levels of KBrO3 in all investigated bread samples exceeded the permissible limit set by the American Food and Drug Administration FDA (0.02 μg/g).